Optimization of Photovoltaic Cells Using Copper-Aluminium Electrodes and Magnesium Sulfate-Based Gel Electrolytes - Yanni, Fitri; Rahadian Zainul (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2025)
Photovoltaic cells are devices that can convert sunlight energy into electrical energy by applying the photovoltaic principle. Indonesia is a country located on the equator that receives a lot of sunlight every year. However, so far the source of electrical energy comes from fossil fuels whose availability is limited. So a material is needed that can improve the performance of photovoltaic cells in producing electrical energy. The purpose of this study was to review the advantages of using Cu-Al electrodes and MgSO4 electrolytes and to find factors that affect the efficiency or performance of photovoltaic cells. This article includes references to articles from 2018 to 2025. The results showed that the use of Cu-Al electrodes and MgSO4 electrolytes can increase cell efficiency. In addition, Cu-Al and MgSO4 are materials that are easy to find and cheap so that they can reduce the cost of making photovoltaic cells compared to other conventional materials that have quite high prices. It is hoped that researchers can utilize this material considering that it has great potential to produce energy in future life.